Electrodeposited Binder‐Free Antimony−Iron−Phosphorous Composites as Advanced Anodes for Sodium‐Ion Batteries. Issue 21 (31st October 2019) - Rong, Wen‐Qian; You, Jin‐Hai; Zheng, Xiao‐Mei; Tu, Guo‐Ping; Tao, Shan; Zhang, Peng‐Yue; Wang, Yun‐Xiao; Li, Jun‐Tao
Abstract: The limited availability and rising cost of lithium have motivated research into sodium as an alternative ion for rechargeable batteries. However, anode development for such sodium‐ion batteries (SIBs) has advanced slowly. Herein, novel binder‐free ternary Sb−Fe−P composites were synthesized through a controllable electrodeposition method and were examined as prospective anode materials for sodium‐ion batteries (SIBs). The Sb47 Fe39 P14 electrode exhibited a high desodiation capacity of 431.4 mA h g −1 at 100 mA g −1 with a capacity retention of 97.8% during the 200 th cycle. Further, this anode delivered a high rate capacity (245.8 mA h g −1 at 2000 mA g −1 ). The promising Na‐ion storage, cycle and rate performance of the Sb47 Fe39 P14 electrode are mainly ascribed to the synergistic effect of its microstructure and active/inactive metal matrix. A kinetics investigation revealed that the rate capability of the Sb47 Fe39 P14 electrode can be attributed to the combination of primary pseudocapacitive and secondary solid‐state diffusion contributions. The results of this study should enable the development of a controllable, scalable electrodeposition strategy and help explore other metallic composites with excellent lifespans and high rate capabilities for practical SIB applications. Abstract : Winning strategy: Ternary Sb−Fe−P alloys are prepared through cost‐effective electrodeposition. The Sb47 Fe39 P14 electrode exhibits a high desodiation capacity of 431.4 mA h g −1 at 100 mA g −1 with a capacity retention of 97.8% during the 200 th cycle. The optimum Sb47 Fe39 P14 electrode shows excellent Na storage properties. The results should enable the development of a controllable, scalable electrodeposition strategy and help explore other metallic composites with excellent lifespans and high rate capabilities for practical sodium‐ion battery applications.